2021
DOI: 10.5965/223811712012021010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of abscission of reproductive structures in common bean access

Abstract: Genotypes from the Andean and Mesoamerican gene pool can present contrasting behavior for reproductive structures fixation. The subject of this study was to determine the dynamics associated with the abscission of reproductive structures for common bean accesses from Andean and Mesoamerican gene pools in protected cultivation conditions. The experiment was carried out in a greenhouse, using seven common bean accesses from Embrapa Arroz e Feijão and the experimental design consisted of a randomized complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is more evident with cultivar 'Purple Royalty' which significantly differs in un-marketable yields in 2016 and 2017. Orsi et al (2021) found variable flower and pod abscission dynamics in different gene pools and genotypes of common beans and recorded certain bean characteristic to be highly significant in their studies, such as the amount of days to begin flowering, the flowering period, percentage of aborted pods and number of harvested pods. This study did not show a consistent positive relationship between yields and pod quality with respect to different planting dates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is more evident with cultivar 'Purple Royalty' which significantly differs in un-marketable yields in 2016 and 2017. Orsi et al (2021) found variable flower and pod abscission dynamics in different gene pools and genotypes of common beans and recorded certain bean characteristic to be highly significant in their studies, such as the amount of days to begin flowering, the flowering period, percentage of aborted pods and number of harvested pods. This study did not show a consistent positive relationship between yields and pod quality with respect to different planting dates.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference was reported (Nemeskéri et al, 2018) in stomatal density on both leaf surfaces between the green-podded and yellow-podded snap bean varieties, during flowering and pod development, under water deficiency and concluded that under non-irrigated conditions, stomatal resistance measured during flowering had a large effect on the individual pod yield. Orsi et al (2021) reported variable flower and pod abscission dynamics in different gene pools and genotypes of common beans. Vega, Chapman & Hall (2001), reported that changes to the management of planting season or cultivar always resulted in corresponding changes in pod and seed number.…”
Section: Introductionmentioning
confidence: 99%